(untitled) (Window of Public Health Journal, 2026)
Technological advancements have advanced rapidly in the era of globalization, especially in the nickel mining industry. These developments undeniably have both positive and negative impacts. One negative impact is the pollution of liquid waste with hazardous heavy metals, both naturally occurring and artificially produced. Therefore, control is necessary. The purpose of this study was to determine the effectiveness of activated charcoal from kumea wood powder in reducing heavy metal levels, especially Cr6+ and Total Cr in wastewater in one of the nickel mining industries in East Luwu Regency. This study used an experimental research design with a pre-test and post-test at two representative sampling locations. The results showed that the higher the concentration of HCl activator, the greater the effectiveness in reducing heavy metal levels. This occurred at an HCl concentration of 0.8 M, but the results were inconsistent: at 1 M, it did not contribute much.